Pengaruh Variasi Putaran Pisau Potong Dan Geometri Mata Pisau Potong Mesin Shredder Penghancur Batang Kelapa Sawit - Fajri, Aidil; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Recently, the utilization of palm stem waste has been studied and explored by many researchers. One of them is the use of small pieces of palm stem as material for making particle board and laminated board. Processing of palm stems into small pieces can be processed by crusher system method. The shredder machine is the type of crusher machine, which incorporate with a rotating cutting of sharp blades that can destroy palm stem. However, his research did not get the optimal result because of limited research done to see the capabilities of the machine. To get optimal result need more research about crushing system, this research was to optimize the performance a shredder machine with some modifications for the engine system such as variations in the round cutter blade and geometry of cutter blade shredder machine. This research used experimental method to investigate the optimal result for crushing of the palm stem. Then, effect of variations the round cutter blade and geometric of cutting blade were tested in some conditions. Therefore, the result of this research might be expected to produce the optimal small pieces of palm stem.Keywords: Waste of palm stem, Shredder machine, Optimal results.